The Pandemic Economy: Exploring the change in new business license activity in Chicago, USA from March – September, 2020 - Credit, Kevin; van Lieshout, Emma (REGION, 2021)
Since its emergence in 2019, the worldwide spread of the novel coronavirus SARS-CoV-2 (COVID-19) has created a vast economic crisis as government lockdowns place considerable strain on businesses of all kinds – particularly those that rely on face-to-face contact, such as retail restaurants, and personal services. Given the recent emergence of the virus and lags in data collection and publication, the highest-quality fine-grained spatial datasets on economic behavior will not reflect virus-related impacts for at least a year. At the same time, in order to make evidence-based decisions on policies regarding continuing lockdown and/or re-opening policies, local governments and researchers need to understand neighborhood-level economic effects much sooner than that. This paper makes use of the point-level Chicago Business License dataset, which is updated on a weekly basis, to examine the impact of the COVID-19 pandemic on new business activity in the City of Chicago. The results indicate that on average, from March to September 2020, total monthly new business starts have declined by 33.4% compared to the monthly average of new starts in the City from January 2016 to December 2019. Food service and retail businesses have been hardest hit during this period, while chains of all types have seen larger average declines in new startup activity than independent businesses. These patterns demonstrate interesting intra-urban spatial heterogeneity; ZIP codes with the largest pandemic-related declines in new business activity tend to be have larger rates average rates of new business creation to begin with and also have less dense, diverse, and walkable built environments (defined in more detail below), while, interestingly, observed COVID-19 case rates do not appear to have an individually-significant impact on new business deficits.